Torque Teno Virus as a Potential Biomarker for Complications and Survival After Allogeneic Hematopoietic Stem Cell Transplantation - Pradier, Amandine; Masouridi-Levrat, Stavroula; Bosshard, Carine; Dantin, Carole; Vu, Diem-Lan; Zanella, Marie-Céline; Boely, Elsa; Tapparel, Caroline; Kaiser, Laurent; Chalandon, Yves; Simonetta, Federico; Roosnek, Eddy (Frontiers in Immunology, 2020)
Impaired immune reconstitution after allogeneic hematopoietic stem cell transplantation (HSCT) contributes to increased risk of cancer relapse and infection resulting in significant morbidity and mortality. Unfortunately, effective strategies to functionally assess the quality of immune reconstitution are still missing. Quantification of in vivo replication of the ubiquitous, non-pathogenic virus Torque Teno Virus (TTV) has been reported in small series as a test to functionally evaluate the quality of post-transplant immune reconstitution. In the present study, we analyzed by quantitative PCR TTV titers in plasma samples from a large cohort of 168 allogeneic HSCT recipients. Our analysis confirms that TTV titers peaked at 100 days post-transplant, followed by progressive normalization thereafter. Negative correlation of TTV titers with T cell absolute numbers during the first year post-transplant points to the restoration of an active anti-TTV immunity. Univariable and multivariable linear regression analysis demonstrated that donor CMV positive serostatus, donor type and immune suppression resulting from GVHD treatment affected the restoration of anti-TTV immunity. Importantly, higher TTV titers at 100 days after transplantation were associated with worse overall survival and higher risk of acute GVHD and infections. Our results provide new insights into the factors affecting the dynamics of TTV replication and indicate that TTV is a potentially useful biomarker to assess immune reconstitution and to predict complications and outcomes of allogeneic HSCT.